1988
DOI: 10.1136/jcp.41.6.694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of faecal preservation and staining methods in the diagnosis of acute amoebiasis and giardiasis.

Abstract: SUMMARY The use of a faecal preservative and several staining methods, together with formalin ether concentration, were evaluated for the improved diagnosis of intestinal amoebiasis and giardiasis in 1285 patients with diarrhoea or dysentery and from asymptomatic controls. All samples were screened by three wet mount techniques. Thirty eight specimens ofdiarrhoeal or dysenteric stool were preserved in polyvinyl alcohol (PVA) and stained by trichrome and Spencer and Monroe short iron haematoxylin stain. Thirty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…The cysts are ovoid or ellipsoid and measure 11-15 mm in diameter. Trophozoites are approximately the same size, with 2 anteriorly placed nuclei and 8 flagella best visualized by staining with trichrome or with the iron hematoxylin method [39,40].…”
Section: New Diagnostic Methods For Potentially Treatable Causes Of Pmentioning
confidence: 99%
“…The cysts are ovoid or ellipsoid and measure 11-15 mm in diameter. Trophozoites are approximately the same size, with 2 anteriorly placed nuclei and 8 flagella best visualized by staining with trichrome or with the iron hematoxylin method [39,40].…”
Section: New Diagnostic Methods For Potentially Treatable Causes Of Pmentioning
confidence: 99%
“…dispar (63, 64, 138a, 164, 171, 229). Shetty and Prabhu found that D'Antoni's iodine was much better than saline or buffered methylene blue for detection of E. histolytica cysts while saline and buffered methylene blue were equally good for detection of E. histolytica trophozoites (206). There are several factors that adversely affect the results of microscopy.…”
Section: Microscopymentioning
confidence: 99%
“…which do not float well because of their high specific gravity. Nevertheless, according to some authors they should also be used especially for identification of protozoan parasites [ 16 ],[ 28 ] or serve as ‘all-round-method’ for all parasite stages [ 24 ],[ 29 ]. Another recently established method (FLOTAC) has been shown to be a sensitive technique for diagnosis of parasitic infections in reptiles [ 30 ] but requires a specially developed apparatus.…”
Section: Introductionmentioning
confidence: 99%